The market research toolbox a concise guide for beginners - McQuarrie, Edward F. (Los Angeles SAGE, 2016)
"An ideal resource for busy managers and professionals seeking to build and expand their marketing research skills, The Market Research Toolbox, Fourth Edition describes how to use market research to make strategic business decisions. This comprehensive collection of essential market research techniques, skills, and applications helps readers solve real-world business problems in a dynamic and rapidly changing business atmosphere. Based on real-world experiences, author Edward F. McQuarrie gives special attention to business-to-business markets, technology products, Big Data, and other web-enabled approaches. Readers with limited time or resources can easily translate the approaches from mass markets, simple products, and stable technologies to their own situations. Readers will master background context and the questions to ask before conducting research, as well as develop strategies for sorting through the extensive specialized material on market research"--Provided by publisher.
Keywords: Marketing research -- Methodology